Strategi Komunikasi Pemasaran Anjungan Taman Mini Indonesia Indah Sebagai Media Promosi Pariwisata Indonesia - Della Khadijjah Chrishma Anugerah; Mohamad Syahriar Sugandi (Jurnal Komunikasi dan Bisnis, 2018)
Tourism as one source of foreign exchange, which makes the need for promotion for Indonesian tourism is increasing. Taman Mini Indonesia Indah as a tourist place that can provide a complete picture of the whole of Indonesia through its pavilions that fully reflect the picture of a province in accordance with the original object or culture. This research uses qualitative research method, Qualitative Research Type in this research is case study research. Case study data were obtained by interviews, observations, and documents. Marketing Communication Strategy implemented by Taman Mini Pavilion aims to introduce, preserve, and develop Indonesian culture where TMII position itself as Show-Window of Indonesian Culture.